A kinetic study on the conversion of methane to higher hydrocarbons in a radio-frequency discharge - Savinov, SY; Lee, H; Song, HK; Na, BK (KOREAN INSTITUTE CHEMICAL ENGINEERS, 2004)
This study investigated methane conversion with direct current discharge at low pressure in a radio frequency. The main gaseous products of the reaction were ethane, ethylene, acetylene and propane. This study was concentrated on the influence of discharge conditions on the conversion of methane to higher hydrocarbons. Reaction temperature, electron density and mean residence time were calculated from experimental data and mathematical relations. The maximum conversion of the methane was about 45% with the pure methane as a reactant. Ethane was the main product when the reaction occurred in the glow discharge. Ethane selectivity decreased with the increase of the gas temperature. The kinetics of reactions was also analyzed from possible reaction equations and various rate constant data. Consequently, the dissociation constant and the density of radicals could be obtained at any experimental conditions.
Keywords: DIELECTRIC-BARRIER DISCHARGE; DECOMPOSITION; CO2